The Agency Myth: Persistence in Individual Explanations for Gender Inequality. (21st December 2020) - Carian, Emily K; Johnson, Amy L
Abstract: We leverage a unique longitudinal dataset—98 interviews with 30 college students—to investigate young people's explanations for gender inequality over time and the implications of those explanations. Through five waves and four years of interviews, we show that young people struggled to internalize structural explanations, instead favoring explanations that conceptualized gender as an individual attribute. Individual perspectives were so intransigent because of respondents' adherence to what we call the agency myth, the latent cultural idea that individuals, particularly women, have the power to overcome gender inequality through strategic behaviors. The agency myth offered young people a sense of self-efficacy, but prevented their imagining broader solutions for social change. Those who were able to think structurally did so only after rejecting the agency myth. This article shows how the durability of individualist perspectives contributes to persistent gender inequality by privileging individualized solutions over more effective structural ones. We discuss how individual subscription to the agency myth is structured by young people's intersecting identities, and how the agency myth can be applied to other axes of inequality.